Relasi Agama dan Negara untuk Pencapaian Tujuan Pemerintahan - Ikang Putra Anggara; Alip Susilowati Utama (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2020)
ABSTRACT The issue that has not been resolved since the beginning of Indonesian independence is the relationship between religion, especially Islam, and the State. Some examples recorded in history include the rebellion known as Darul Islam / Indonesian Islamic Army (DI / TII) and the Revolutionary Government of the Republic of Indonesia. The most recent case that shows the tension between religion and the State in Indonesia is related to efforts to handle cases of radicalism and terrorism which are felt by Muslims to seem to corner and stigmatize Islamic groups only. The purpose of this research is to analyze the relationship between religion and the state according to the perspective of Islamic organizations and religious groups in Ogan Komering Ulu Regency which is measured from the view of the informants regarding the ideal relationship between Islam and the state, the existence of the Indonesian nation-state based on Pancasila, interpreting the existence of radicalist and terrorist groups in Islam, as well as alternative efforts in dealing with the problem of radicalism and terrorism in the State of Indonesia. Keywords: Religion; Country; Radicalism; Terrorism